Morphological characterization and phylogenetic placement of Xiuguozhangia sahyadriensis (Pseudoberkleasmiaceae, Pleosporales), a new species from the Western Ghats, India - Paraparath, Sruthi O.; Rajeshkumar, Kunhiraman C.; Réblová, Martina; Jeewon, Rajesh; Lad, Sneha S.; Karunarathna, Samantha C.; Tibpromma, Saowaluck; Castañeda-Ruiz, Rafael F. (Phytotaxa, 2025)
In this study, a new species, Xiuguozhangia sahyadriensis, collected on decaying twig from the southern Western Ghats of Kerala, India. The new taxon is morphologically distinct from other Xiuguozhangia species, characterised by its longer and rarely branched conidiophores, as well as distinctive dimensions of conidia and conidiogenous cells. Based on Phylogenetic analyses of combined LSU, ITS, SSU, tef1α and rpb2 sequence data, using Maximum Likelihood and Bayesian Inference, X. sahyadriensis formed a sister taxon to X. broussonetiae within Pseudoberkleasmiaceae. This is the first study to present multigene sequence data of a Xiuguozhangia species from India.